The Relationship Between Parental Smoking Habits and the Incidence of ARI in Toddlers at the Integrated Health Post (Posyandu) in Bani Amas Village, Bengkayang - Virawati Virawati; Annisa Rahmawati; Uji Kawuryan; Ridha Mardiyani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Acute Respiratory Tract Infection (ARI) is a disease of the upper or lower respiratory tract. This disease is contagious and causes a range of signs and symptoms, from asymptomatic and mild infections to more severe and potentially fatal illnesses, depending on the pathogen. The presence of family members who smoke in the home is a contributing factor to health problems within the family, such as respiratory disorders. Moreover, it may increase the incidence of ARI, especially in toddlers. The study determined the relationship between parental smoking habits and the incidence of ARI in the Integrated Health Post (Posyandu) of Bani Amas Village, Bengkayang. Using a quantitative method with a cross-sectional approach, with a sample of 54 respondents, data were collected by distributing questionnaires and analyzed using the Spearman Rank test. The study showed no relationship between parental smoking habits and the incidence of ARI in toddlers at the Integrated Health Post (Posyandu) of Bani Amas Village, Bengkayang, where the result was a p-value of 0.054 (>0.05). The results of this study indicate that smoking habits are not the only factor that influences the incidence of ARI in toddlers. Still, cigarettes only provide vulnerability to ARI in toddlers because they contain harmful substances that can damage the respiratory system during the developmental stage.